Association between preconception anti-androgen therapy and pregnancy outcomes of patients with PCOS: A prospective cohort study - Zhang, Xiaowei; Miao, Huazhang; Zhou, Jiahe; Chen, Yuan; Ou, Yanlan; Song, Yue; Peng, Xiuhong; Li, Yuancheng; Li, Li (Frontiers in Endocrinology, 2023)
Background: Polycystic ovary syndrome (PCOS) not only increases fertility challenges for women of reproductive age, but also leads to increased complications during pregnancy and even affects the birth weight of newborns. Also, hyperandrogenemia is associated with lower pregnancy rates and lower live birth rates and may even play a role in preterm delivery and pre-eclampsia in patients with PCOS. However, it is still controversial whether PCOS patients are treated with androgen-lowering therapy before pregnancy. Objective: To assess the effect of anti-androgen therapy prior to ovulation induction on maternal and infant pregnancy outcomes in patients with PCOS. Methods: Prospective cohort study. Results: A total of 296 patients with PCOS were enrolled in the study. The prevalence of adverse pregnancy outcomes, and Neonatal complications was lower in DRSP group than in NO-DRSP groups (DRSP vs. NO-DRSP: adverse pregnancy outcomes, 12.16% vs. 27.03%, P=0.001; Neonatal complications, 17.16% vs. 36.67%, P＜0.001). No significant difference was found in maternal complications. Further subgroup analysis revealed that PCOS with pretreatment decreased the risk of preterm delivery (2.99% vs. 10.00%; Adjusted RR, 3.80; 95% CI, 1.19-12.13), pregnancy loss (9.46% vs. 18.92%; Adjusted RR, 2.07; 95% CI, 1.08-3.96), low birth weight (0.75% vs 7.50%; Adjusted RR, 12.08; 95% CI, 1.50-97.31), fetal malformations(1.49% vs. 8.33%; Adjusted RR, 5.63; 95% CI, 1.20-26.33).There were no significant differences in the incidence of DM and PIH as pregnancy complications between the two groups (P>0.05). Conclusion: Our findings suggest that preconception androgen-lowering therapy in patients with PCOS improves adverse pregnancy outcomes and reduces neonatal complications.